Understanding Customer Loyalty: The Roles of Customer Relationship Management, Company Reputation, and Customer Satisfaction - Sutrisno Wibowo; Rizal Diaz Al-Ishlah (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to analyze the effect of Customer Relationship Management and Company Reputation on Customer Loyalty through Customer Satisfaction. The subjects of this study were users of J&T Express delivery services. This study used primary data with a sample of 185 respondents selected using a purposive sampling technique. Data were collected through an online questionnaire distributed via Google Form. Data analysis in this study was conducted using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method, processed with SmartPLS software. The results show that Customer Relationship Management and Company Reputation have a positive and significant effect on Customer Satisfaction. Customer Relationship Management does not have a significant direct effect on Customer Loyalty, whereas Company Reputation has a positive and significant effect on Customer Loyalty. In addition, Customer Satisfaction has a positive and significant effect on Customer Loyalty. The results also show that Customer Relationship Management and Company Reputation affect Customer Loyalty through Customer Satisfaction. These findings indicate that Customer Satisfaction plays an important role in bridging the effect of Customer Relationship Management and Company Reputation on Customer Loyalty.